The role of collectors in the flotation of partially oxidised copper ores - Hangone, Gregory (Department of Chemical Engineering, 2014)
The effects of xanthates, dithiophosphates, dithiocarbamates and mixtures of these collectors on the froth flotation performance of partially oxidised and oxidised copper sulphide ores were investigated in this study. More specifically, the role of the functional groups of the collectors, their dosages and the effect of collector mixtures and their dosages were investigated. Batch flotation tests were used to assess the performance in terms of mass-water recovery, sulphur grade-recovery, copper grade-recovery and acid soluble copper grade-recovery relationships and the Klimpel rate constant for copper recovery. Flotation characteristics of bornite rich Carolusberg copper sulphide ore from Okiep Copper Company (1.8% copper) and bornite and chalcopyrite rich ore from Palaborwa Mining Company (0.58% copper) were compared.